2015
DOI: 10.1371/journal.pone.0116087
|View full text |Cite
|
Sign up to set email alerts
|

The “Good Cop, Bad Cop” Effect in the RT-Based Concealed Information Test: Exploring the Effect of Emotional Expressions Displayed by a Virtual Investigator

Abstract: Concealing the possession of relevant information represents a complex cognitive process, shaped by contextual demands and individual differences in cognitive and socio-emotional functioning. The Reaction Time-based Concealed Information Test (RT-CIT) is used to detect concealed knowledge based on the difference in RTs between denying recognition of critical (probes) and newly encountered (irrelevant) information. Several research questions were addressed in this scenario implemented after a mock crime. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 107 publications
(161 reference statements)
1
6
0
Order By: Relevance
“…Previous RT-CIT experiments which have used images of objects as stimuli have shown large CIT effect sizes ranging from d = 1.05 to 1.24 (Suchotzki et al, 2015;Varga et al, 2015;and Visu-Petra et al, 2016). Given that the current study was the first reported scene-based RT-CIT, a smaller, but still relatively large, effect size was estimated 1 .…”
Section: Methods Participantsmentioning
confidence: 72%
See 2 more Smart Citations
“…Previous RT-CIT experiments which have used images of objects as stimuli have shown large CIT effect sizes ranging from d = 1.05 to 1.24 (Suchotzki et al, 2015;Varga et al, 2015;and Visu-Petra et al, 2016). Given that the current study was the first reported scene-based RT-CIT, a smaller, but still relatively large, effect size was estimated 1 .…”
Section: Methods Participantsmentioning
confidence: 72%
“…To date, RT-CIT studies have typically used word stimuli (Eom, Sohn, Park, Eum, & Sohn, 2016;Hu, Evans, Wu, Lee, & Fu, 2013;Kleinberg & Verschuere, 2016;Noordraven & Verschuere, 2013;Seymour & Kerlin, 2008;Seymour, Seifert, Shafto, & Mosmann, 2000;Seymour & Fraynt, 2009;Verschuere, Kleinberg & Theocharidou, 2015;Verschuere, Crombez, Degrootte, & Rosseel, 2010;Visu-Petra, Miclea, & Visu-Petra, 2012;Visu-Petra, Varga, Miclea, & Visu-Petra, 2013;and Visu-Petra, Miclea, Buş, & Visu-Petra, 2014), with only a handful having used images. Moreover, those that have presented images have only used pictures of discrete objects that can be easily recognized and labeled (Visu-Petra, Jurje, Ciornei, & Visu-Petra, 2016;Varga, Visu-Petra, Miclea, & Visu-Petra, 2015;Suchotzki, Verschuere, Peth, Crombez, & Gamer, 2015). For example, Visu-Petra and colleagues (2016) used images of objects (backpacks, watercolors, pencils, and erasers) to test the effectiveness of the RT-CIT in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, if a presented face in fact co-determines physiological responding in the CIT, then the specific connotation of that face for the subject becomes a central question. The impact of facial emotional expressions representing a virtual investigator on reaction times in a CIT was examined by Varga et al (20). Interestingly, the mere presence of a virtual investigator’s neutral face led to an increase in overall but not differential reaction times, whereas emotional expression in this face was found to differentially increase reaction times to probe items.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with better inhibitory skills had faster absolute lie RTs but RT difference scores showed no correlation with any executive function measure. Despite the intuitive involvement of arousal and emotion mechanism in deception, behavioral experiments report mixed results about the association between deceptive RTs and measures of anxiety (Visu-Petra et al, 2012), personality (Verschuere & in ´t Hout, 2016; Visu-Petra et al, 2014) or motivation (Kleinberg & Verschuere, 2016; Varga, Visu-Petra, Miclea, & Visu-Petra, 2015).…”
Section: Introductionmentioning
confidence: 99%